Answer: -43
==================================================
Step-by-step explanation:
We'll use PEMDAS here.
Focus on the stuff in the parenthesis first. We multiply 7 and 1 to get 7*1 = 7
Then we add on -5 getting -5+7 = 2
The stuff in the parenthesis turns into 2
We go from this
(-5+7*1) - 9*5
to this
2 - 9*5
From here we multiply 9 and 5 to get 45, then subtract like so
2-45 = -43
-----------------------------
So here's the step by step picture
(-5 + 7*1) - 9*5
(-5 + 7) - 9*5
(2) - 9*5
2 - 9*5
2 - 45
-43